Mortality Risk Factors Among People Living with HIV Receiving Second-line Antiretroviral Therapy in Rural China - Kang, Qiujia; Pan, Wanqi; Ma, Yanmin; Wang, Dongli; Jia, Huangchao; Guo, Huijun; Sang, Feng; Xu, Liran; Xu, Qianlei; Jin, Yantao (Current HIV Research, 2024)
Background: Second-line antiretroviral therapy (ART) was introduced in Henan Province in 2009. The number of people living with human immunodeficiency virus (HIV) starting this therapy is increasing. Objective: This study aimed to investigate the survival and factors affecting mortality among this group. Methods: We conducted a retrospective cohort study of people living with HIV (PLHIV) who switched to second-line ART between May 1, 2010, and May 1, 2016, using the Kaplan-Meier method and Cox proportional hazards models. Results: We followed 3,331 PLHIV for 26,988 person-years, of whom 508 (15.3%) died. The mortality rate was 1.88/100 person-years. After adjusting for confounding factors, we found being a woman (hazard ratio (HR), 0.66; 95% confidence interval (CI) 0.55–0.79), > 50 years old (HR, 2.69; 95% CI, 2.03-3.56), single/widowed (HR, 1.26; 95% CI, 1.04-1.52), having > 6 years of education (HR, 0.78; 95% CI, 0.65-0.94), Chinese medicine (HR, 0.75; 95% CI, 0.52-0.96), liver injury (HR, 1.58; 95% CI, 1.19-2.10), and CD4+ T cell count <200 cells/μl (HR, 1.94; 95% CI, 1.47-2.55), or 200-350 cells/μl (HR, 1.37; 95% CI, 1.03-1.82) were associated with mortality risk. Conclusions: We found lower mortality among PLHIV who switched to second-line ART than most previous studies. The limitations of a retrospective cohort may, therefore, have biased the data, and prospective studies are needed to confirm the results. Moreover, Chinese medicine combined with second-line ART shows potential as a treatment for HIV.
Keywords: Human immunodeficiency virus